2017
DOI: 10.1177/2332858417690511
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Curriculum Effects on Student Achievement in California

Abstract: We estimate relative achievement effects of the four most commonly adopted elementary mathematics textbooks in the fall of 2008 and fall of 2009 in California. Our findings indicate that one book, Houghton Mifflin's California Math, is more effective than the other three, raising student achievement by 0.05 to 0.08 student-level standard deviations of the Grade 3 state standardized math test. We also estimate positive effects of California Math relative to the other textbooks in higher elementary grades. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 33 publications
2
51
0
1
Order By: Relevance
“…Curricula set goals for the knowledge and skills that children should acquire in an educational setting, and support educators’ plans for providing the day-to-day learning experiences to cultivate those skills with items such as such as daily lesson plans, materials, and other pedagogical tools (Gormley 2007, Ritchie and Willer 2008). While social scientists have recently begun to consider the effects of curricula in other settings (Jackson and Makarin 2016, Koedel et al 2017), there exists little or no evidence about which early childhood curricula are best for whom.…”
Section: Introductionmentioning
confidence: 99%
“…Curricula set goals for the knowledge and skills that children should acquire in an educational setting, and support educators’ plans for providing the day-to-day learning experiences to cultivate those skills with items such as such as daily lesson plans, materials, and other pedagogical tools (Gormley 2007, Ritchie and Willer 2008). While social scientists have recently begun to consider the effects of curricula in other settings (Jackson and Makarin 2016, Koedel et al 2017), there exists little or no evidence about which early childhood curricula are best for whom.…”
Section: Introductionmentioning
confidence: 99%
“…A handful of non-experimental studies have identified moderate effects of textbooks on student achievement gains (upwards of 0.14 SD). Koedel and co-authors used matching methods and school-level aggregate achievement to measure textbook efficacy in three states: California, Florida, and Indiana (Bhatt & Koedel, 2012;Bhatt, Koedel & Lehmann, 2013;Koedel et al, 2017). Given the large number of texts observed in California and Florida, the analysts used a two-step process in these states.…”
Section: Non-experimental Studiesmentioning
confidence: 99%
“…In California, state law requires that schools report on textbook adoptions each year as part of school accountability report cards (Hutt & Polikoff, 2018). Our raw data came from reports hosted on the California Department of Education website, in which schools reported the title of textbooks they adopted by subject and grade (see Koedel et al, 2017, for additional information). Those data allowed us to identify the math textbook adopted for 87 percent of elementary schools in our sampling frame (n = 5,107 of 5,841 schools; see Table 1).…”
Section: Textbook Adoptionsmentioning
confidence: 99%
See 2 more Smart Citations